Penguatan Peran Ziswaf dalam Menyongsong Era SDGs: Kajian Filantropi BMT Tamzis Wonosobo - Nurma Khusna Khanifa (Universitas Muhammadiyah Magelang, 2018)
The way to alleviate the poverty in the community, family, and individuals to prosperous condition and to alleviate the burden of daily living needs is a real practice of philanthropy. This is the relevance between the objectives of zakat, infaq, shadaqah, and waqf (ziswaf) and Sustainable Development Goals (SDGs) towards the achievement of development goals. The movement focuses on 6 issues including: without poverty, without hunger, quality education, decent work and economic growth, reduced inequality, and environmental cleanliness. It means that ziswaf is a pressure on the existence of community assets. As an effort to fund to distribute (social function), as well as control function. In order to have a practical and valuable impact, Islamic philanthropy must have a relationship between the purpose and essence of the Shari'a in the form of maqashid syarîah to encourage social welfare and the economy. As the inherent institution of Baitul Mal Tamzis, the concept of a creative philanthropy approach is used to increase the scope and sustainability of institutional impacts and provide institutional specific roles with specific institutions and target communities both consumptive and productive